No Evidence of Re-infection or Person-to-Person Transmission in Cured COVID-19 Patients in Guangzhou, a Retrospective Observational Study - Xu, Gang; Liu, Feng; Ye, Min; Zhao, Jun; Li, Qing; Feng, Congrui; Hu, Yudong; Li, Yueping; Shi, Haiyan; Zhang, Fuchun; Tong, Yuwei; Ma, Wei (Frontiers in Medicine, 2020)
ABSTRACT Objectives To clarify the clinical features of cured patients with coronavirus disease (COVID-19) and the relevance of IgM and IgG testing. Methods A total of 187 cured COVID-19 patients with antibody test were followed up every two weeks. Assessment for general condition, symptoms, epidemiological contact history, polymerase chain reaction (PCR) assay, and antibody tests were performed and recorded. Information from Guangzhou CDC was also screened. Results There were 33 (17.6%) patients with negative results for IgG and 35 (18.7%) patients with positive results for IgM. PCR assay was positive in 10 (5.3%) patients during the follow-up. Neither IgG nor IgM results showed a relationship with PCR test results (all P > 0.05). Neither re-infection nor person-to-person transmission was found in the cured patients. Factors associated with appearance of antibody comprised hospitalization days (OR: 1.06, 95%CI: 1.02-1.11, P = 0.006) and antibiotics treatment (OR: 3.50, 95%CI: 1.40-8.77, P = 0.007) . Conclusions In our study, neither re-infection nor person-to-person transmission was found in cured patients with COVID-19. Additionally, neither IgG nor IgM can be used to replace the PCR test in cured patients.